A high areal capacity sodium-ion battery anode enabled by a free-standing red phosphorus@N-doped graphene/CNTs aerogel. Issue 51 (1st June 2022) - Sun, Yi; Wu, Qiujie; Zhang, Kuanxin; Liu, Yongchao; Liang, Xin; Xiang, Hongfa
Abstract : Illustration of the structure of the free-standing P@NGCA electrode and its sodium storage performance. Abstract : A novel and facile strategy for fabricating red phosphorus@nitrogen doped graphene/carbon nanotube aerogel (P@NGCA) is proposed as a free-standing anode for high energy sodium-ion batteries. Owing to an optimized structure of red P uniformly confined in porous NGCA with high conductivity and mechanical stability, the free-standing P@NGCA anode exhibits outstanding sodium storage performance with a high areal capacity of 3.3 mA h cm −2 and superior initial Coulombic efficiency of 80%.